2023
DOI: 10.3390/jof9030376
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Polymerization Promoting Proteins (TPPPs) of Aphelidiomycota: Correlation between the Incidence of p25alpha Domain and the Eukaryotic Flagellum

Abstract: The seven most early diverging lineages of the 18 phyla of fungi are the non-terrestrial fungi, which reproduce through motile flagellated zoospores. There are genes/proteins that are present only in organisms with flagellum or cilium. It was suggested that TPPP-like proteins (proteins containing at least one complete or partial p25alpha domain) are among them, and a correlation between the incidence of the p25alpha domain and the eukaryotic flagellum was hypothesized. Of the seven phyla of flagellated fungi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…An interesting point is that not all Chytridiomycota TPPP/p25alpha domain can be found in the same clade. The unusual (different from the species phylogeny) position of Caulochytrium TPPP was found earlier, too [ 22 , 23 ]; the reason for it is not known. Another case is the species included in the dotted box in Figure 6 labeled with ‘2’ following the species name.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…An interesting point is that not all Chytridiomycota TPPP/p25alpha domain can be found in the same clade. The unusual (different from the species phylogeny) position of Caulochytrium TPPP was found earlier, too [ 22 , 23 ]; the reason for it is not known. Another case is the species included in the dotted box in Figure 6 labeled with ‘2’ following the species name.…”
Section: Discussionmentioning
confidence: 85%
“…The very same alga has other fungal parasites, Aphelidium tribonematis [ 32 ] and Paraphelidium tribonematis [ 33 ], which belong to the phylum Aphelidiomycota and did not lose their flagellum [ 34 ]. Based on the genomic/proteomic data published in references [ 11 ] and [ 35 ], it has been shown that both of them possess a fungal-type TPPP ( Figure S1 and [ 22 ]). However, species of another genus of the phylum, Amoeboaphelidium , are characterized by the presence of a non-motile pseudocilium [ 10 , 36 ], similarly to sanchytrids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the sequences of seed plants (Spermatophyta) deposited in the NCBI databases were systematically examined for the presence of the p25alpha domain. This domain is found in TPPP-like proteins, which are absent in land plants [ 10 , 23 ]. The reason for this is that the p25alpha domain is connected to the presence of flagellum/cilium, which was lost from most land plants during evolution [ 11 ].…”
Section: Discussionmentioning
confidence: 99%